Pengetahuan Ibu Hamil Tentang Tanda Bahaya Kehamilan di Puskesmas II Denpasar Selatan - Ni Komang Tri Agustini (STIKES ADVAITA MEDIKA TABANAN, 2022)
The Maternal Mortality Rate (MMR), which is calculated per 100,000 births in Indonesia, still shows a slow decline. Some of the causes of maternal death are due to complications that can arise through pregnancy alarms. The purpose of this study was to determine the mother's knowledge in recognizing the danger signs of pregnancy. This research is a cross-sectional type of descriptive analysis to see a description of the knowledge of pregnant women in recognizing the danger signs of pregnancy and the factors that influence them. This study used consecutive sampling technique. The sample consisted of 80 pregnant women who performed antenatal care at Puskesmas II Denpasar Selatan. The results showed that most (81.3%) pregnant women had less knowledge in recognizing the danger signs of pregnancy. The results also stated that there was no significant relationship between age, gravida and occupational status with the level of knowledge of pregnant women in recognizing danger signs of pregnancy.